DAMPAK PENILAIAN UNTUK PEMBELAJARAN TERHADAP MOTIVASI DAN KETERLIBATAN SISWA - Magdalena, Ina; Andreani, Melia Gita; Nurhasanah, Silvia; Ushaybiah, Zahwa Muflihah (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2023)
Assessment in the context of learning has an important role in influencing student motivation and engagement. Effective assessment can have a significant positive impact on student's motivation to learn and their level of engagement in the learning process. Through formative assessments that provide constructive and informative feedback, students can correct their shortcomings and see their progress first-hand, which directly influences their motivation to continuously strive to improve achievement. Assessments that reward and recognize students' achievements can also increase their motivation. In addition, assessments that actively involve students in the assessment process, such as project- or portfolio-based assessments, and assessments that encourage social interaction, can increase student engagement. However, it is important to ensure that effective assessment is fair, objective, and differentiated so that each student gets feedback that is relevant to their needs and level of development. In conclusion, effective assessment should be viewed as a learning tool that encourages student motivation and engagement in the learning process.